Serum Vascular Endothelial Growth Factor in Pregnant Women with Different Types of Assisted Reproductive Techniques - Zainab Y. Ejam; Şevki Adem; Asmaa Kadhim Gatea (Medical Journal of Babylon)
Background: Vascular endothelial growth factor (VEGF) is crucial for the implantation of a fertilized egg and for the development of placental blood vessels. This study was conducted to detect the serum VEGF level of pregnant with different types of assisted reproductive techniques in relation to the age group, body mass index (BMI), and type of infertility. Objectives: The aim of this study was to determine the levels of serum VEGF in different types of assisted pregnancy. Materials and Methods: Enzyme-linked immunosorbent assay was used for the detection of VEGF levels in the serum of pregnant women in the first trimester of pregnancy with a spontaneous pregnancy (SP), pregnant women by intrauterine insemination (IUI) or in vitro fertilization-embryo transfer (IVF), in comparison with nonpregnant women (NP). Results: A highly significant increase was seen in the serum VEGF within the different studied pregnant groups compared to that of NP and no difference between IUI and IVF (P < 0.01). Statistical analysis showed a nonsignificant relation between the VEGF serum levels and the increase in age or BMI (P > 0.05). No significant differences were seen in VEGF serum levels between pregnant women with primary or secondary types of infertility (P > 0.05). Conclusion: Statistical analysis showed a significant increase in the serum of VEGF in IUI and IVF comparison to SP groups, whereas there is no difference between IUI and IVF. Age, BMI, and type of infertility showed no significant effect on serum VEGF levels.